(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2022)
Residential houses such as flats located near industrial areas are vulnerable to the threat of high-intensity dust, thereby, exposing the occupants to Sick Building Syndrome (SBS) in the form of health problems, especially in the upper respiratory system. Therefore, this research was conducted to find appropriate design solutions to minimize dust from entering buildings through the application of geometric planes as a form of defense. It is also important to note that dust is closely related to the direction of the wind which is its conveying medium. This led to the determination of the right geometric shape to be applied as a dust barrier in the building facade. Moreover, this research was based on the force-based framework which proposes a form-refine-assembly stage consisting of several methods to determine the shape through simulation and evaluation associated with existing theories. The results were able to determine the position and shape of the facade area to serve as the barrier to the arrival of dust. The design is expected to be integrated into the shape and landscape layout of buildings to reduce dust in the site area.